Speculative design as a tool for anticipatory innovation in global healthcare - Yukhnova, K. (ХНУРЕ, 2025)
The rapid technological progress of the post-pandemic era reveals deep vulnerabilities within global healthcare systems. Fragmentation, workforce shortages, cyber threats, and supply-chain fragility are not isolated failures but interconnected signals of a system under pressure.
Keywords: Speculative design; global healthcare